Predicting Collisionless Equlibria in Dark Matter Simulations - Ragan, Robert (Proceedings of the Wisconsin Space Conference, 2016)
By using a transformation from phase-space variables to a set of orthogonal Hermite-Legendre polynomials, the dynamics of one-dimensional self-gravitating systems has been reduced to a linear set of equations. This transformation changes the long-range forces into local interactions in the new problem.Â This makes it possible to determine the steady-state solutions by projecting the initial conditions into the time-independent solutions.